Algae-based plastic: preparation of moldable bioplastic from cladophora (Bangladesh Journal of Botany, 2026)
The research presents a method for converting green algae into a moldable bioplastic. Specifically, the present processes used a green alga Cladophora sp. combined with myrrh to obtain the moldable bioplastic. The moldable bioplastic can form a composite, optionally with other environmental friendly materials, to obtain eco-friendly biodegradable products.Bangladesh J. Bot. 55(2): 433-436, 2026 (June)